Krisis ekologi di indonesia: Dampak eksploitasi sumber daya alam dan upaya pemanfaatan berkelanjutan - Abdillah, Dani (Maliki Interdisciplinary Journal, 2025)
Indonesia has abundant natural resources, ranging from forest products, marine products, to minerals such as nickel. However, this great potential has not been balanced with sustainable management. In recent decades, excessive exploitation of natural resources has caused environmental damage and triggered an ecological crisis in various regions. One case of concern is nickel mining in Raja Ampat, Southwest Papua an area known as a world conservation area. The presence of the mining industry threatens the ecosystem, causing deforestation, water pollution, land damage, and the loss of endemic flora and fauna habitats. Not only that, indigenous communities are also affected socially and culturally. This research was conducted using a literature study and qualitative descriptive approach, referring to academic literature, the views of environmental figures, and national online media. It was found that weak supervision, unclear environmental laws, and minimal community participation were the main causes. Lack of environmental education also worsens the condition. For this reason, policy reform, strengthening regional supervision, involvement of indigenous communities, and application of ESG principles are needed so that mining continues to pay attention to environmental sustainability and ecosystem sustainability.